Retrograde intrarenal surgery with intelligent control of renal pelvic pressure for staghorn calculi: a case report - He, Xiaolong; Huang, Xin; Zhai, Qiliang; Song, Leming; Deng, Xiaolin (Frontiers in Medicine, 2024)
Percutaneous nephrolithotomy is the gold standard treatment for staghorn calculi. However, this study reviews a case of an almost complete removal of staghorn calculi following one session of retrograde intrarenal surgery with intelligent control of renal pelvic pressure (RIRS-ICP). A 45 years-old female patient with an 8.3 × 4.5 cm complete staghorn stone was infected with Proteus mirabilis. Two sensitive antibiotics, piperacillin tazobactam and etimicin, were administered for 3 days. Semirigid 7/8.4 Fr ureteroscope was used to treat the renal pelvis and upper calyceal calculi for 57 min. A 550 μm holmium laser fiber with 2.0 J × 30 Hz was set. Next, a disposable flexible ureteroscope of 8.4 Fr was used to address residual middle and lower calyx stones for 94 min. A 200 μm holmium laser fiber with 1.0 J × 30 Hz was set. The renal pelvis pressure was controlled within 15 mmHg. A 2 mm CT scan on the first postoperative day showed inferior caliceal residue of approximately 1.0 × 0.6 cm. No complications occurred. This suggests that RIRS-ICP is a safe and effective treatment for staghorn calculi.